Learning Management System Built Using the MERN Stack - H. P. A. H. Piyumantha; D. V. S. Prabhash; T. K. Weerasinghe; R. T. K. Weerasiri; D. I. De Silva; S. M. D. T. H. Dias (International Journal of Engineering and Management Research, 2022)
Web based applications play a main role in our day-to-day life and therefore, it is important to ensure the quality and reliability of web applications. With the sudden increase in use of web based applications for online and distant learning, it is important to address existing issues in current Learning Management Systems (LMS), so that users can benefit from a better, uninterrupted learning experience. This work mainly contributes to understanding how the MERN stack can be efficiently used in building a reliable and secure LMS that will provide its services free of charge so that students are provided with a free and uninterrupted learning experience. An LMS that is equipped with user handling functionality, managing courses and course materials, and maintaining a library, has been the focus of the study that resulted in producing this paper. The work also includes reasoning as to why the MERN stack was selected for developing the proposed system.